2019
DOI: 10.3390/ijms20236101
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1/MCPIP-1 Signaling Modulates the Effects of IL-1β in Renal Cell Carcinoma through ER Stress-Mediated Apoptosis

Abstract: In renal cell carcinoma (RCC), interleukin (IL)-1β may be a pro-metastatic cytokine. However, we have not yet noted the clinical association between tumoral expression or serum level of IL-1β and RCC in our patient cohort. Herein, we investigate molecular mechanisms elicited by IL-1β in RCC. We found that IL-1β stimulates substantial monocyte chemoattractant protein (MCP)-1 production in RCC cells by activating NF-kB and AP-1. In our xenograft RCC model, intra-tumoral MCP-1 injection down-regulated Ki67 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
1
12
1
Order By: Relevance
“…MAPK Interacting Serine/Threonine Kinase 2 (MKNK2) is a protein-coding gene, primarily associated with IL-1 signaling pathway and ERK signaling pathway. Interestingly, the interleukin-1 family is associated with the growth and metastasis of several cancers (21,22). The present study also Novel Biomarkers in Gastric Cancer found a positive correlation of MKNK2 with memory B cells, regulatory T cells (Tregs), and CD8 T cells in gastric cancer, all of which are reported to be strongly associated with tumors (23)(24)(25).…”
Section: Discussionsupporting
confidence: 67%
“…MAPK Interacting Serine/Threonine Kinase 2 (MKNK2) is a protein-coding gene, primarily associated with IL-1 signaling pathway and ERK signaling pathway. Interestingly, the interleukin-1 family is associated with the growth and metastasis of several cancers (21,22). The present study also Novel Biomarkers in Gastric Cancer found a positive correlation of MKNK2 with memory B cells, regulatory T cells (Tregs), and CD8 T cells in gastric cancer, all of which are reported to be strongly associated with tumors (23)(24)(25).…”
Section: Discussionsupporting
confidence: 67%
“…40,41 IL-1β stimulation could enhance ER stress-induced apoptosis sensitivity in renal cell carcinoma through the induction of PERK and CANX expression. 41 The activation of the EFGR pathway could activate caspase-8-mediated cleavage to the CANX cytosolic domain. The cleaved CANX cytoplasmic domain moves into the nucleus where it binds to PIAS3 (a natural inhibitor of STAT3), thereby preventing PIAS3 from binding to STAT3.…”
Section: Discussionmentioning
confidence: 98%
“…These molecules are essential to the stable formation of DC and T‐cell synapses 39 . In addition, CANX expression may similarly increase the sensitivity to ER stress‐induced apoptosis 40,41 . IL‐1β stimulation could enhance ER stress‐induced apoptosis sensitivity in renal cell carcinoma through the induction of PERK and CANX expression 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, tumorigenesis is identified at 2-3 weeks when the local tumor mass size was about l cm 3 . Tumor growth status was determined as follows [15]: poor tumor growth was defined as an average tumor weight of < l g or if the tumor weight was <400 mg in mice with 20% overall tumor weight. Nude mice with poor tumor growth that met these criteria were considered a failed model and were excluded.…”
Section: Immunofluorescencementioning
confidence: 99%